The mental health effects of informal caregiving emerging research and opportunities - Gavin Ware, Debra 1960-; Johnson, Tarnue Carver (IGI Global, 2019)
"This book explore the influence of presumed positive psychological factors on caregivers, such as self-efficacy, social support, spirituality, resilience, and leisure participation on the subjective well-being of the informal caregiver"...Provided by publisher